2023
DOI: 10.1017/laq.2022.91
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Visualization: Remote Sensing Applications in Prehispanic Settlements to Understand Ancient Anthropogenic Land Use and Occupation in the Sierra Nevada de Santa Marta, Colombia

Abstract: Archaeology is increasingly employing remote sensing techniques such as airborne lidar (light detection and ranging), terrestrial laser scanning (TLS), and photogrammetry in tropical environments where dense vegetation hinders to a great extent the ability to understand the scope of ancient landscape modification. These technologies have enabled archaeologists to develop sophisticated analyses that overturn traditional misconceptions of tropical ecologies and the human groups that have inhabited them in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In contrast to focused studies that examine niche aspects of human settlements like ancient sites [29], [30], rural areas [31], and informal settlements [32], [33], this paper presents a comprehensive analysis of human settlement dynamics across Mexico. By covering a country with diverse settlement scenarios, this study offers an inclusive and varied understanding of settlement patterns, developing strategies applicable to various countries with different geographical contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to focused studies that examine niche aspects of human settlements like ancient sites [29], [30], rural areas [31], and informal settlements [32], [33], this paper presents a comprehensive analysis of human settlement dynamics across Mexico. By covering a country with diverse settlement scenarios, this study offers an inclusive and varied understanding of settlement patterns, developing strategies applicable to various countries with different geographical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Osorio et al [29] utilize remote sensing techniques like lidar and photogrammetry to reveal significant ancient landscape changes in prehispanic settlements in Colombia, challenging the notion of these areas being pristine. Abate et al [30] also use similar technologies for analyzing medieval settlements in Italy, focusing on producing detailed 3D and 2D data to uncover and interpret hidden sites.…”
Section: A Human Settlements Detectionmentioning
confidence: 99%
“…This approach allows us to deal with some of the limitations identified in pixel‐based classification approaches, such as the production of speckle noise by high local spatial heterogeneity between neighboring pixels in fine spatial resolution imagery and the difficulty of including topological relationships in classifications (Dorren et al, 2003; Drăguţ & Blaschke, 2006; Hay et al, 2005; Herrera‐Fernandez et al, 2004). OBIA is a relatively new technique within the discipline that has been mainly used for remote sensing archaeological applications, such as surface cover classifications that enable the automated identification and extraction of archaeological features from large‐scale data sets (Davis, 2019; Magnini & Bettineschi, 2019; Magnini et al, 2017; Rodriguez et al, 2023; Verhagen, 2012). More recently, however, scholars have tested the use of OBIA and other image analysis approaches at the artifact scale for archaeological purposes, extracting morphological (e.g., Lamotte & Masson, 2016), compositional (e.g., Hein et al, 2018), and mineralogical features (e.g., Aprile et al, 2014; Hofmann et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The authors found that 93% of the incised gullies originated from pre-existing channels in 1968, and that their development process was mainly characterized by channel merging and gully wall widening. Despite the advanced capabilities of current LiDAR technology to penetrate cloud cover and areas with dense vegetation, it still encounters limitations with regard to pristine forested regions and expansive watersheds [20]. The interpretation results often underestimate the actual outcomes.…”
Section: Introductionmentioning
confidence: 99%